Influence of circumferential gap on the axial compressive behaviour of circular CFDST stub columns: Tests, numerical analysis and design method - Pei-Jia Dai; Rui Wang; Hui Zhao; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

A salivary elicitor MsPDI3 from Mythimna separata triggers plant defense responses - Jin-Da Wang; Huan-Tai Lin; Lin Li; Yao-Hui Chen; Ran Wang; Honglin Feng; San-Ji Gao (Insect Biochemistry and Molecular Biology, 2026)

Axial compression behavior of circular CFDST stub columns with localized corrosion: Testing, numerical modeling and design - Guangdi You; Hui Zhao; Rui Wang; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Thermodynamic compatibility and conformational adaptability enable the matrix-adaptive protection of glycated pea protein isolate-curcumin nanoparticles in frying oils - Zhi-feng Tan; Cong Sun; Shi-hui Zhao; Zhen-wen Shao; Da-yong Zhou; Liang Song (Food Chemistry, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Surfactant-assisted hierarchical assembly of debranched starch nanoparticles: Insights into desolvation-driven molecular and crystalline ordering - Da-Hui Kim; Xing Zhou; Jong-Yea Kim (Carbohydrate Polymers, 2026)

Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Integrated geophysical investigation of a contaminated abandoned industrial site validated by borehole sample analysis: A case study in northeastern Shanghai, China - Shi-Jin Feng; Jin-Hui Shu; Xiao-Lei Zhang; Qi-Teng Zheng; Zhen-Xing Sun; Wen-Da Wang (Engineering Geology, 2026)

Ecological and social contexts of scorpion stings in Manaus, the largest metropolis of the Brazilian Amazon - Zehev S. Benzaken; Joseir Saturnino Cristino; Haicha Benzaken; Jacqueline Sachett; Erica da Silva Carvalho; Yasmin da Silva Mendes; Handerson da Silva Pereira; Alexandre Silva-Neto; Fan Hui Wen; Maria das Graças Vale Barbosa Guerra; Wuelton Monteiro (Toxicon, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Effect of vertically non-uniform tidal currents on VLOC squat prediction in shallow harbor fairways - Da Hui; Guangyao Wang; Shengchang Jia; Qianyu Wang; Yilin Huang; Jinshan Zhu (Ocean Engineering, 2026)

Correction: MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2026)

Independent risk factors for refractory mycoplasma pneumoniae pneumonia in children: a multivariate analysis - Qi Guo; Hui Guo; Jie-Jie Chen; Xian-Zong Da; Xia Xu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Study on the relationship between surface deformation and internal fracturing of tunnel surrounding rock under uniaxial loading with multiple blasting disturbances - Tian-Xiao Chen; Shi-Da Xu; Ben-Guo He; Yuan-Hui Li; Jian-Yu Peng (Tunnelling and Underground Space Technology, 2026)

Differential light spectrum regulation of oogenesis and spermatogenesis in Plectropomus leopardus - Hui Ding; Lin Li; Da Zheng; Mingjian Liu; Jinyang Xie; Binglin Li; Yuli Li; Zhenmin Bao; Bo Wang; Jingjie Hu (Aquaculture, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

The effects and mechanisms of corn zein hydrolysate on intestinal inflammation in mouse and organoid models - Kangkai Chen; Ping Liu; Zirui Wang; Hui Xia; Ligang Yang; Da Pan; Guiju Sun; Wang Liao (Food Bioscience, 2026)

Neural Circuit with Top-Down Inhibitory Feedback Outperforms Optimal Bayesian Integration in Multisensory Integration - Yelin Dong; Hongzhi You; Yuxiu Shao; Yong Gu; KongFatt Wong-Lin; Da-Hui Wang (Neuroscience Bulletin, 2026)

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

Engineering pore structure of bamboo-derived porous carbons via pyrolysis behavior of various organic potassium salts for efficient nitrate removal by capacitive deionization - Rencheng Li; Menghan Pu; Weilong Xiao; Yufeng Da; Luwei Miao; Yang Bao; Ke Li; Qiulin Yang; Wenqing Chen; Hui Sun (Desalination, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Experimental and numerical investigations on hysteretic behaviour of tapered RAC-filled high-strength double-skin steel tubular columns - Yupeng Guo; Rui Wang; Hui Zhao; Yunhe Wang; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Determination of anisotropic effective thermo-mechanical properties of leafy vegetables via X-ray CT and finite element modelling using forward and inverse analyses - Hui Gao; Zhiwei Zhu; Da-Wen Sun (Journal of Food Engineering, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Clinical Evidence on the Health Benefits and Safety of Probiotic Lacticaseibacillus rhamnosus: A Systematic Review - Yu Yang; Jing Sui; Wang Liao; Shaokang Wang; Da Pan; Guiju Sun; Peng Gao; Xuesong Xiang; Hui Xia (Probiotics and Antimicrobial Proteins, 2026)

A Randomized, Double-Blind, Placebo-Controlled Study on Probiotic Treatment for Halitosis: Novel Insights into Glucose and Phosphorus Metabolism - Ji Hye Choi; Sehyeon Song; Min Ji Jang; Md Ariful Haque; Hye Eun Lee; Da Hui Kim; Yeo Ju Kim; Ja Won Cho; Jin Seok Moon; Keon Heo; Myeong Soo Park; Seockmo Ku (Probiotics and Antimicrobial Proteins, 2026)
Halitosis, or bad breath, is associated with oral microbial imbalances and the production of volatile sulfur compounds (VSCs). While existing treatments target pathogenic bacteria or oral health indicators, they may not address the underlying systemic complexity. This study explored the efficacy of Complex OK oral probiotics containing Lactobacillus gasseri HHuMIN D and L. paracasei OK in mitigating halitosis by evaluating VSC levels and metabolic markers. A 12-week, randomized, double-blind, placebo-controlled clinical trial was conducted involving 80 participants, 70 of whom completed the study in South Korea (KCT0009894). The participants were selected based on the presence of 2 of 3 pathogenic oral bacteria ( F. nucleatum , P. gingivalis , and P. intermedia ) and baseline VSCs > 2.0 ng/10 mL. Exclusion criteria included systemic diseases, recent antibiotic/probiotic use, and severe dental conditions. Oral health, VSCs, and metabolic markers were assessed using paired t -tests, ANCOVA, and Wilcoxon rank-sum tests. Despite unchanged oral health indicators and levels of harmful bacteria, probiotic supplementation showed efficacy in maintaining microbial balance. Significant reductions in H₂S and total VSCs were observed in the experimental group compared to the placebo ( P < 0.05). No significant changes were observed in oral health indices or levels of harmful oral bacteria, but the experimental group showed a significant decrease in blood glucose ( P = 0.009) and an increase in phosphorus levels ( P < 0.05). This study provides the first published evidence linking systemic metabolic regulation to halitosis reduction, suggesting that probiotics mitigate bad breath through glucose and phosphorus metabolism rather than by direct bacterial inhibition. Further research is needed to confirm these findings and to explore the underlying mechanisms.

Advances in understanding the MicroRNA-transcription factor regulatory network governing terpenoid biosynthesis in medicinal plants - Jingyi Xu; Yue Shi; Xiaoqian Xie; Yueting Xie; Jing Tian; Yue Ren; Yuan Li; Da Li; Chunmei Yang; Qile Zhou; Jinhui Man; Hui Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Tree Diversity Enhances Nitrogen Retention and Accelerates Phosphorus Cycling - Tao Wang; Zaipeng Yu; Minghui Da; Mengjuan Wang; Hui Jia; Lulu He; Xiaohua Wan; Zhiqun Huang; Yann Hautier (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) cycling are crucial for terrestrial ecosystem productivity and carbon sequestration. While biodiversity is known to regulate soil N and P availability, the mechanistic linkages between biodiversity and fundamental processes of nutrient cycles remain unclear. This knowledge gap limits our capacity to model ecosystem biogeochemical responses to biodiversity loss. Using a large‐scale tree diversity experiment in subtropical China, we examined how tree species richness regulates ecosystem nutrient cycling in a region with N sufficiency but P limitation. We found that increased tree species richness enhanced N retention by boosting plant N stock and recycling, while reducing soil NO 3 − leaching and N 2 O emissions. These shifts, coupled with a reduction in soil δ 15 N, demonstrate tighter N cycling. Concurrently, tree species richness increased soil acid phosphatase activity, foliar P resorption efficiency, and plant P storage, synergistically accelerating ecosystem P cycling. Our integrated findings provide direct experimental evidence that tree diversity regulates both N and P cycling, offering valuable insights into how plant diversity can mitigate nutrient imbalances and promote ecosystem resilience to nutrient limitations.

Spatial identification of priority restoration-protection regions based on ecosystem services-climate-human framework on the Tibetan Plateau - Zhengrong Yuan; Hui Zhao; Da Wei; Meihong Wang; Ruoming Li; Xiaodan Wang (Journal of Environmental Management, 2026)

Energy efficiency and thermochemistry of sulfur-containing coal gangue, a coal-based solid waste - Hui-yong Niu; Chen-hong Zhou; Hai-yan Wang; Gong-da Wang; Jiu-ling Zhang; Yan-xiao Yang; Xiaodong Yu (Fuel, 2026)

Ultrasonic-vacuum combined effects on Antarctic krill oil oxidation stability: Potential mechanisms of oxygen reduction and influence on reverse micelle - Xue-Chen Pei; Fa-Wen Yin; Chang-Qiang Leng; Xin-Miao Wang; Qian Wang; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Gyrotropic magnetic effect in black phosphorus irradiated with bicircular light - Fangyang Zhan; Xin Jin; Da-Shuai Ma; Jing Fan; Peng Yu; Dong-Hui Xu; Rui Wang (Science Bulletin, 2026)

Occurrence, distribution, and risk assessment of antibiotics in post-harvest and drained ponds of Sheyang River estuary in Jiangsu Province: Implications for sustainable aquaculture management - Wenqian Shan; Shiya Gu; Wangrong Cui; Xinyun Feng; Xin Song; Jianwei Dong; Hui Xie; Da Li (Journal of Contaminant Hydrology, 2026)

Chitosan-SNAP composite coating with sustained NO release for microbial killing and tomato preservation - Jie Chen; Hui Zhang; Yuxin Lin; Jinyu Liu; Yisong Chen; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Food Chemistry, 2026)

Geographical effects on ambient air pollution and clinical visits for respiratory diseases: a case study with three exposure scenarios - Hui-Ju Wen; Shu-Li Wang; Chih-Da Wu; Mao-Chang Liang (Atmospheric Pollution Research, 2026)

The Effect of Density Difference on the Sedimentation Dynamics of Two Spherical Particles in Side-by-Side and Tandem Configurations - Da Hui; Xiang Ji; Baizhuang Chen; Mingfu Tang; Lixin Xu (Journal of Marine Science and Engineering, 2025)
Complex fluid–particle interactions are ubiquitous in natural environments and engineering applications, with their underlying mechanisms often attributed to interparticle attraction and repulsion. To understand the interaction mechanism between the dual particles, this study examines the setting process of dual particles using the Immersed Boundary-Lattice Boltzmann Method (IB-LBM), with a focus on the effect of the density difference between particles. Two typical configurations—tandem and side-by-side—are considered in the analysis. In the tandem configuration, when ρLP/ρTP 1, kissing between two particles is mainly determined by the density of LP. Whether kissing occurs between the two particles depends on a critical value ρLP/ρTP=1.2:1.14. Although the LP’s attraction to the TP strengthens with increasing LP density, beyond this certain threshold, this attraction becomes insufficient for the TP to catch up with the LP. In a side-by-side configuration with two particles of different densities, their interaction evolves from initial attraction to subsequent repulsion. This phenomenon is not observed in pairs of particles with identical density. Moreover, with increasing density difference between the particles, the attractive effect from the higher-density particle on the lower-density one strengthens, whereas the repulsive interaction between them gradually weakens. When the particle density ratio reaches 1.4:1.14, the lateral migration of the particles becomes very small; although they still interact with each other, the effect becomes extremely weak. This work systematically elucidates the influence of density disparity on particle interaction, providing insights into understanding more complex multiparticle system dynamics.

Determination of porosity and permeability correlation of leafy vegetable based on X-ray computed tomography and cell segmentation - Hui Gao; Zhiwei Zhu; Da-Wen Sun (Journal of Food Engineering, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Combustion Behavior and Thermal Disaster Quantification of Weathered Water-Saturated Coal in an Oxygen-Poor Environment of Goaf - Hui-yong Niu; Hao-liang Zhu; Qing-qing Sun; Hai-yan Wang; Gong-da Wang; Lu-lu Sun (Natural Resources Research, 2025)

Identification of grape H3K27 methyltransferase genes and their expression profiles during grape fruit ripening - Ding-Ding Zuo; Hao-Ting Sun; Lu Yang; Fang-Hui-Zi Shang; Da-Long Guo (Molecular Biology Reports, 2025)

Low self-fertilization rate and putative self-incompatibility in Codonopsis pilosula (Campanulaceae) - Hui Zhang; Shaoming Shi; Lujie Yang; Fan Zhao; Zhiqi Wang; Ying Zhang; Jing Fang; Yujie Zhang; Lingling Da (Genetic Resources and Crop Evolution, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Siloxene coupled graphene anode membrane with Zn-ion intercalation for all-solid-state Zn-ion hybrid supercapacitors - Erhui Zhang; Da Xie; Yuchen Hong; Zhenzhen Hui; Yongsheng Zhou; Shengbiao Zheng; Jiahao Guo; Zirong Li; Jie Chen; Jing Tang (Chemical Engineering Journal, 2025)

Automatic quantification, grading and five-year prediction of myopic fundus tessellation: a multi-center, longitudinal deep learning study - Wen-Da Zhou; Li Dong; Wen-Xue Li; Li-Jian Fang; Tong Ma; Lie Ju; Zhao-Hui Wang; Yuan Luo; Wanli Miles Zhang; Xian-Gang Chang; Zong-Yuan Ge; Jost. B. Jonas; et al. (Science China Life Sciences, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

Study on the role and function of RRS1 in cutaneous squamous cell carcinoma - Zhan-Yan Pan; Zhi-Nan Shi; Qiong Wu; Ting-Ting Hu; Xiao-Hui Mo; Da-Ke Dong; Qiang Ju (Tissue and Cell, 2025)

Unveiling the key drivers and formation pathways for secondary organic aerosols in an eastern China megacity - Fei Zhang; Jiasi Shen; Da Xu; Jiandong Shen; Yiming Qin; Ruifang Shi; Jing Wei; Zhengning Xu; Xiangyu Pei; Qian Tang; Hui Chen; Bingye Xu; et al. (Journal of Hazardous Materials, 2025)

Mechanical response of tunnel surrounding rock under blasting disturbance with different stress conditions based on acoustic emission and digital image correlation - Tian-xiao Chen; Shi-da Xu; Ben-guo He; Yuan-hui Li; Han Lei (Engineering Geology, 2025)

Atomic-scale frustrated Lewis pairs in ultrathin BiOCl nanosheets: Dynamic oxygen vacancy engineering for efficient CO2 photoreduction - Da Wu; Dexin Liu; Hui Luo; Jiaqiang Wang; Yeliang Dong (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Seismic Data Interpolation by AVO-Preserving Hyperbolic Radon Transform Using FISTA and Polynomial Fitting - Sheng-chao Wang; Han-feng Liu; De-fu Zhang; Hui Sun; Wei Zhang; Song-da Ji (Applied Geophysics, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Decoding the mechanism of flavor improvement mediated by inoculated starter cultures in low-salt HuangYuXiang: From lipids to volatile flavor compounds - Ji Wang; Chengzhen Nie; Wei Yang; Xu-Song Wang; Da-Yong Zhou; Xu-Hui Huang; Lei Qin (Food Bioscience, 2025)

Shaking table tests and numerical simulations of museum showcases subjected to floor motions - Pei Liu; Da-Cheng Hui; Hao-Tian Chen; Yuan-Ming Zhang (Engineering Structures, 2025)

Optimizing zonal management framework suitable for mountain ecosystems by linking landscape, ecosystem service capacities and bundles nested - Yunqi Hao; Yihe Lü; Hui Dang; Da Lü; Chenjun Du; Yi Wang; Luning Wang; Xiaofeng Wang; Xuan Li; Bojie Fu (Journal of Environmental Management, 2025)

Phosphoproteomics reveals essential regulatory roles of phosphorylation in marine oligotrophic bacteria - Yu Zhang; Yao-Hui He; Zhang-Xian Xie; Zhuo-An Bai; Guo-Sheng Hu; Ming-Hua Wang; Stephen J. Giovannoni; Da-Zhi Wang (Marine Life Science & Technology, 2025)
Oligotrophic bacteria with reduced genomes have relatively few transcriptional regulators and are thought to rely more than other bacteria on post-transcriptional regulation to respond to environmental stimuli. SAR11 bacteria are the most abundant group of heterotrophic bacteria in marine planktonic systems and are a model for understanding genome reduction in other free-living microorganisms. Here, we report a comprehensive, quantitative protein phosphorylation profile for SAR11 strain HTCC1062 grown under various environmentally relevant conditions, including light/dark cycles, temperature differences, and nutrient limitations, to investigate phosphorylation dynamics in this streamlined organism. Nearly half of proteins encoded by the genome were detected in phosphorylated forms under at least one condition. 1014 Ser/Thr/Tyr phosphorylation sites were observed in 1576 phosphopeptides from 555 phosphoproteins. Protein phosphorylation was concentrated in proteins for functions associated with nutrient acquisition and growth, such as ABC transporters, RNA polymerase, and ribosomal proteins. Prominent patterns in protein phosphorylation were detected across a range of culture conditions. In these cells, which previously have been shown to continuously express nearly their entire proteome, protein phosphorylation was more dynamic than protein abundance, supporting the hypothesis that post-transcriptional regulation by protein phosphorylation might play a large role in modulating protein activity. Our findings support a regulatory model characterized by minimal variation in protein expression but extensive protein phosphorylation. This model diverges from bacterial regulatory paradigms reliant on transcriptional control, and may be relevant to understanding other abundant heterotrophs with reduced genomes.

Swimming of a self-propelled fishlike body in the slurry - Da Hui; Jinshan Zhu; Guiyong Zhang; Zhijing Xu (Ocean Engineering, 2025)

Revealing the oxidation mechanism of Antarctic krill oil induced by metal ion: Focusing on the influence of reverse micelles - Xue-Chen Pei; Fa-Wen Yin; Meng-Ling Jin; Xin-Miao Wang; Hui-Lin Liu; Liang Song; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Vitamin C prevents myricetin degradation in boiling water by reducing ortho-quinone intermediates - Shengxiong Chen; Fan Zhang; Aline Priscilla Gomes da Silva; Jesus Simal-Gandara; Hui Cao (Food Chemistry, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Binders with cationic semi-interpenetrating networks for sodium-ion batteries under extreme conditions - Chen-Hui Yang; Chi-Hon Leung; Lan-Fang Que; Fu-Da Yu; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Study on mechanism behind browning of Antarctic krill upon hot air drying and its control - Chao Guo; Xiang-Bo Zeng; Bo Peng; Fa-Wen Yin; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Characteristics of secondary microseisms generated in the Bohai Sea and their impact on seismic noise - Kang-Da Yin; Xiao-Gang Zhang; Xiao-Jun Li; Guo-Liang Mao; Xing-Xing Zhang; Xiao-Hui Jia (Applied Geophysics, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Flexural fatigue behavior of FRP-reinforced UHPC tubular beams - Tian-Hui Fan; Jun-Jie Zeng; Xianwen Hu; Jun-Da Chen; Ping-Ping Wu; Hui-Tao Liu; Yan Zhuge (Engineering Structures, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Mechanism of differentiated and targeted catalysis in complex lipid system under lipase and lipoxygenase mediation - Liang Wang; Zheng Zhou; Ji Wang; Xu-Song Wang; Da-Yong Zhou; Lei Qin; Xu-Hui Huang (Food Chemistry, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Electrospun 1D Al-LLZO incorporated PVDF-HFP composite electrolyte with fast Li+ pathway derived from highway-traction effect for high performance lithium metal batteries - Joo-Young Han; Sunghoon Kim; Dae Ung Park; Dongwoo Kang; Ji-Hui Oh; Da-Eun Hyun; Dong-Won Lee; Hwiyun Im; Jong-Min Oh; Sang-Mo Koo; Jeonghyun Kim; Jong Ho Won; et al. (Chemical Engineering Journal, 2025)

Harnessing the polysaccharide production potential to optimize and expand the application of probiotics - Dong-Xu Ma; Hui-Juan Cheng; Hui Zhang; Shuo Wang; Xiao-Tao Shi; Xin Wang; Da-Chun Gong (Carbohydrate Polymers, 2025)

ABA-mediated regulation of PME12 influences stomatal density, pore aperture, and heat stress response in Arabidopsis thaliana - Hui-Chen Wu; Shih-Yu Yu; Sandeep Vivek; Yin-Da Wang; Tsung-Luo Jinn (Planta, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Extraction of antimicrobial peptides from pea protein hydrolysates by sulfonic acid functionalized biochar - Min Liu; Xian-Da Hu; Xiang-Yu Huang; Li Wen; Zhou Xu; Li Ding; Yun-Hui Cheng; Mao-Long Chen (Food Chemistry, 2025)

Numerical Simulation of a Marine Landslide in Gas Hydrate-Bearing Sediments Using L-GSM - Da Hui; Guangyao Wang; Yilin Huang; Guixun Zhu; Wenming Li (Journal of Marine Science and Engineering, 2024)
The marine gas hydrates within seabed sediments and their subsequent extraction may cause landslides. Predicting landslides in hydrate-bearing sediments is particularly challenging due to the intricate nature of the marine environment. To address this issue, we have developed a Lagrangian gradient smoothing method (L-GSM) based on gradient smoothing techniques. This approach effectively eliminates the tensile instability inherent in the original Smoothed Particle Hydrodynamics (SPH) method used for modeling solid flow. Then, we applied the L-GSM to investigate the mechanics of hydrate-bearing sediments by integrating a constitutive equation specific to these sediments, which were modeled based on the artificial methane-hydrate-bearing sediment. The robustness and precision of the L-GSM were verified through various numerical examples. Furthermore, we modeled the landslides associated with hydrate-bearing sediments under varying hydrate saturation levels. The numerical findings revealed that hydrate saturation significantly affects the dynamics of landslide movement. These satisfactory results suggest that the L-GSM has the potential to be applied to geotechnical problems associated with hydrate-bearing sediment.

Productivity experienced a more rapid enhancement trend than greenness across the Tibetan Plateau - Ruzhi An; Huaan Jin; Hui Zhao; Da Wei; Wei Zhao; Xiaodan Wang (Science of The Total Environment, 2024)

Numerical investigation of free surface flow impact using an accelerated three-dimensional smoothed particle hydrodynamics - Guiyong Zhang; Xi Yang; Zhifan Zhang; Da Hui; Zhe Sun; Guangqi Liang; Peng Li (Ocean Engineering, 2024)

Relationship between MO/(SiO2+Al2O3) of materials—amorphous gel structure—properties of the one-part FA-Slag-based AAMs - Da-Wang Zhang; Tian-Tian Yang; Xiao-Guang Xu; Yi-Ren Wang; Hui Li (Journal of Environmental Chemical Engineering, 2024)

Comprehensive insights into the organoleptic characteristics attributes of “HuangYuXiang”: Integration of volatilomics, sensomics, macrogenomics, lipidomics, and metabolomics - Ji Wang; Xu-Song Wang; Zichun Zhang; Da-Yong Zhou; Xu-Hui Huang; Lei Qin (Food Chemistry, 2024)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

Spatial and seasonal variations of atmospheric microplastics in high and low population density areas at the intersection of tropical and subtropical regions - Chien-Cheng Jung; Yuan-Chen Chao; Hui-Tsung Hsu; Da-Wei Gong (Environmental Research, 2024)

On the Revival Mechanism of Typhoon Doksuri (2023) Remnants after Its Landfall - Chunyi Xiang; Lin Dong; Yu Lan; Hui Wang; Runling Yu; Xiaoyong Zhuge; Da Liu; Qian Wang (Journal of Meteorological Research, 2024)

Elevated temperature as the dominant stressor on the harmful algal bloom-causing dinoflagellate Prorocentrum obtusidens in a future ocean scenario - Wei-Ping Zhang; Hui Wei; Shuo-Yu Zhang; Shu-Feng Zhang; Yang Zhou; Wen-Jing Sun; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Cyanide content, nutrient composition, physicochemical properties and sensory quality of flaxseed oil bodies prepared from flaxseeds (Linum usitatissimum L.) treated with different heat treatment methods - Rui Zheng; Hui-Lin Liu; Nan-Nan Cui; Jun-Zhuo Zhou; Xin Sun; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Analysis of stage parameters of low-temperature oxidation of water-soaked coal based on kinetic principles - Yun-chuan Bu; Hui-yong Niu; Gong-da Wang; Tian Qiu; Yan-xiao Yang; Lu-lu Sun (Science of The Total Environment, 2024)

Efficient solution-processable OLEDs near BT.2020 red standard enabled by a multiresonant emitter - Hui Wang; Ying-Chun Cheng; Xiao-Chun Fan; Dong-Yang Chen; Xin Xiong; Xiao-Yao Hao; Yi-Zhong Shi; Jia Yu; Da Huang; Jia-Xiong Chen; Kai Wang; Xiao-Hong Zhang (Science Bulletin, 2024)

Novel Sustained Release Azithromycin Resinate Fabricated by One-Pot Ion-exchange Performed in Hydro-alcoholic Solution - Hongyu Liang; Meihui Zhao; Shaoning Wang; Da Wang; Jingxin Gou; Yanjie Bai; Mingyue Shen; Junfeng Wang; Yujie Cheng; Ning Ge; Yi Zhao; Jie Zeng; et al. (AAPS PharmSciTech, 2024)

Numerical Investigation of Oblique Currents’ Effects on the Hydrodynamic Characteristics of Ships in Restricted Waters - Yilin Huang; Da Hui; Mingyu Xia; Guangyao Wang; Jinshan Zhu (Journal of Marine Science and Engineering, 2024)
The influence of oblique currents in narrow and shallow channels causes the fluid flow around ships to become complex. To analyze the hydrodynamic characteristics of a ship in such channels, it is essential to examine the influence of oblique currents on the ship’s hydrodynamic characteristics. In this study, current direction, ship speed, current speed, and water depth were identified as determinants affecting the hydrodynamic characteristics of a ship. Numerical simulations were conducted on a large oil tanker to investigate the effects of these factors on the ship’s hydrodynamic characteristics. The viscous fluid flow was modeled using the unsteady Reynolds-averaged Navier–Stokes (URANS) equations in conjunction with the k-ε turbulence model. The URANS equations were discretized using the finite volume method. The numerical results indicate substantial differences in the hydrodynamic characteristics of ships under oblique current conditions compared to still-water conditions. At a current direction of β = −45°, the direction of the sway force is consistent with that of still water’s sway force, which is an attractive force. The yaw moment at β = −45° changes from a bow-out moment under still-water conditions to a bow-in moment. Conversely, at a current direction of β = 45°, the sway force shifts from an attractive force under still-water conditions to a repulsive force. The yaw moment acts as a bow-out moment, which is consistent with that observed in still-water conditions. Furthermore, the influence of hydrodynamic characteristics on a ship varies significantly with changes in ship speed, current speed, and water depth. To ensure the safe navigation of ships, it is essential to develop and apply comprehensive strategies and countermeasures that account for practical conditions.

Integrating Health and Climate Data to Enhance Snakebite Envenomation Response - Joao Vitor Perez de Souza; Alexandre Vilhena da Silva Neto; Marcos Adriano Garcia Campos; Elle Strand; Wuelton Monteiro; Felipe Murta; Jacqueline Sachett; Fan Wen Hui; Brian McAdoo; Charles Gerardo; Joao Ricardo Nickenig Vissoci (Toxicon, 2024)

Association of Asian dust storms and PM2.5 with clinical visits for respiratory diseases in children - Hui-Ju Wen; Shu-Li Wang; Chih-Da Wu; Mao-Chang Liang (Atmospheric Environment, 2024)

Genome-wide analysis of long non-coding RNAs involved in the fruit development process of Cucumis melo Baogua - Ya-hui Li; Chun Liu; Run-zhe Xu; Yu-peng Fan; Ji-yuan Wang; Hu Li; Jian Zhang; Hui-jun Zhang; Jing-jing Wang; Da-kui Li (Physiology and Molecular Biology of Plants, 2024)

Minimization of heavy metal adsorption in struvite through effective separation and manipulation of flow field - Yazhou Wang; Jinrong Da; Yuchen Luo; Sirui He; Zuocong Tian; Ziyi Xue; Zehao Li; Xianyu Zhao; Desheng Yin; Hui Peng; Xiang Liu; Xiaoning Liu (Journal of Hazardous Materials, 2024)

The effects of an online food waste reduction platform in university canteens in Wuhan, China - Wanqi Du; Li Xue; Da Xu; Hui Zhang; Gang Liu; Huabo Duan; Junjie Dong; Jinyi Chen; Huali Zhang (Journal of Cleaner Production, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Mechanism of color change in Antarctic krill oil during storage - Xiang-Bo Zeng; Fa-Wen Yin; Guan-Hua Zhao; Chao Guo; De-Yang Li; Hui-Lin Liu; Lei Qin; Fereidoon Shahidi; Da-Yong Zhou (Food Chemistry, 2024)

A comprehensive evaluation of lipid profiles and nutritional quality in different animal source muscle tissues - Shuang Cui; Ying Wang; Zheng Zhou; Yu-Ying Zhang; Xu-Hui Huang; Da-Yong Zhou; Lei Qin (Food Bioscience, 2024)

Compensatory effect of lipase on the flavor of lightly-salted large yellow croaker: Integration of flavoromics and lipidomics - Ji Wang; Xu-Hui Huang; Xusong Wang; Hehe Tian; Liang Wang; Da-Yong Zhou; Lei Qin (Food Bioscience, 2024)

Optimizing restoration duration to maximize CO2 uptake on the Tibetan Plateau - Yahui Qi; Da Wei; Zhuangzhuang Wang; Hui Zhao; Jiabin Fan; Jing Tao; Xiaodan Wang (CATENA, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Tailoring raloxifene into single-component molecular crystals possessing multilevel stimuli-responsive room-temperature phosphorescence - Zhichao Pan; Jinming Song; Shasha Zhang; Ping Zeng; Ju Mei; Da-Hui Qu (Science Bulletin, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Programming and validation of a novel green procedure for the production of essential oil from Lavandula angustifolia - Ming-Chi Wei; Wen-Lung Lee; Pao-Hui Huang; Da-Hsiang Wei; Zun-Siao Jheng; Yu-Chiao Yang (Food and Bioproducts Processing, 2024)

Tuning the electrocatalytic activity of MoS2 nanosheets via the in situ hybridization with ruthenium and graphene network - Sk Emdadul Islam; Da-Ren Hang; Chi-Te Liang; Krishna Hari Sharma; Hui-Chun Huang; Mitch M.C. Chou (Chemical Engineering Journal, 2024)

Capacity of community health centers to treat snakebite envenoming in indigenous territories of the Brazilian Amazon - André Sachett; Eleanor Strand; Thiago Serrão-Pinto; Alexandre da Silva Neto; Thais Pinto Nascimento; Sewbert Rodrigues Jati; Gisele dos Santos Rocha; Sediel Ambrósio Andrade; Fan Hui Wen; Manuela Berto Pucca; João Vissoci; Charles J. Gerardo; et al. (Toxicon, 2024)

2D Bi2MoO6 nanosheets immobilized on electrospun 1D LaFeO3 hollow nanofibers: An efficacious direct Z-scheme p-n type heterojunction photocatalyst for removal of organic contaminants under visible-light irradiation - Da Xu; Feng Sun; Feng Liu; Hong Shao; Wurigamula He; Lili Wang; Qianli Ma; Wensheng Yu; Hui Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2024)

Bacoside a inhibits the growth of glioma by promoting apoptosis and autophagy in U251 and U87 cells - Hai-Yun Liu; Yu-Long Ji; Hong Du; Shu-Hui Chen; Da-Peng Wang; Qiao-Li Lv (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Orthogonal dynamic covalent boroxine-crosslinked poly(disulfide) networks for chemically recyclable encryption materials - Mingyu Shi; Chen-Yu Shi; Qi Zhang; Da-Hui Qu (Chemical Engineering Journal, 2024)

The genesis and resource potential of gold deposits in the Liaodong Peninsula - Rixiang Zhu; Jin-Hui Yang; Gongwen Wang; Qingdong Zeng; Guoqiang Xue; Tao Xu; Xinghui Li; Peng Zhang; Da Lei; Guang Zhu (Science China Earth Sciences, 2024)

Molecular and morphological evidences for the hybrid origin of Kushui Rose - Fan Zhao; Ying Wang; Yu-jie Zhang; Kun Sun; Ling-ling Da; Hui Zhang (Genetic Resources and Crop Evolution, 2024)

Integrated surrogate framework for reactive transport simulation of uranium in situ leaching with generative models - Wen-gui Ji; Yue Luo; Bing Wang; Xun Li; Jin-hui Liu; Yan-hong Zhang; Da-ye Liang (Journal of Hydrology, 2024)

Performance of round-ended CFST columns under combined actions of eccentric compression and impact loads - Hui Zhao; Shengqi Mei; Rui Wang; Xu Yang; Wen-Da Wang; Wensu Chen (Engineering Structures, 2024)

Inhibition of nucleotide metabolism with dual-template epitope imprinted nanoparticles for targeted HER2+ tumor therapy - Xing-Hui Ren; Lei Shi; Zi-Bo Ma; Da-Wei Wang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Chemical Engineering Journal, 2024)

Category representation in primary visual cortex after visual perceptual learning - Zhaofan Liu; Yin Yan; Da-Hui Wang (Cognitive Neurodynamics, 2024)

Observations of near-inertial internal wave amplification and enhanced mixing after surface reflection - Kun Liu; Xu Chen; Peng Zhan; Lianglong Da; Hui Wang; Wuhong Guo; Jingyi Liu; Lei Chen; Bing Liu; Guandong Gao; Deyan Tian (Progress in Oceanography, 2024)

Sulfamic acid modified UiO-66 metal-organic framework for biodiesel production: Process optimization using response surface methodology, kinetics, and thermodynamic study - Shiva Prasad Gouda; Da Shi; Sanjay Basumatary; Hui Li; Ramón Piloto-Rodríguez; Samuel Lalthazuala Rokhum (Chemical Engineering Journal, 2024)

Simultaneously tuning oxygen reduction pathway and charge transfer dynamics toward sacrificial agent-free photocatalytic H2O2 production for in-situ water disinfection - Ya-Ya Yang; Hai Guo; Da-Wei Huang; Lu Li; Hui-Yun Liu; Long Sui; Qian Wu; Jing-Jing Zhu; Lei Zhang; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

Analysis of research status and trends on marine benthic dinoflagellate toxins: A bibliometric study based on web of science database and VOSviewer - Jing-Qian Tang; Qian-Hui Shen; Yao-Yao Han; Yang Wu; Xiang-Feng He; Da-Wei Li; Yong Huang (Environmental Research, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Cerina litoralis gen. nov., sp. nov., a novel potential polysaccharide degrading bacterium of the family Flavobacteriaceae, isolated from marine sediment - Ya-Wei Wang; Xin-Hui Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Antonie van Leeuwenhoek, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Tigliane diterpenoids with cytotoxic activities from Croton damayeshu - Rong-Lin Jia; Qian Liang; Jia-Xin Hu; Si-Da Xie; Xiao-Min Su; Wen-Hui Xu (Phytochemistry Letters, 2023)

Microbial communities and their correlation with flavor compound formation during the mechanized production of light-flavor Baijiu - Lu-Jun Luo; Liang Song; Ying Han; Pan Zhen; Da-Yong Han; Xin Zhao; Xin Zhou; Yu-Hua Wei; Hui-Xin Yu; Pei-Jie Han; Feng-Yan Bai (Food Research International, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Integrated volatolomics and metabolomics analysis reveals the characteristic flavor formation in Chouguiyu, a traditional fermented mandarin fish of China - Jia-Nan Chen; Yu-Ying Zhang; Xu-Hui Huang; Meng Dong; Xiu-Ping Dong; Da-Yong Zhou; Bei-Wei Zhu; Lei Qin (Food Chemistry, 2023)

Effect of Clostridium butyricum on intestinal microbiota and resistance to Vibrio alginolyticus of Penaeus vannamei - Chen Wang; Peng-Fei Li; Da-Gang Hu; Hui Wang (Fish & Shellfish Immunology, 2023)

Dead-end forward osmosis as an alternative for deep sludge dewatering: Evaluation method and characteristics analysis - Da-Qi Cao; Hui Liu; Feng Tian; Wen-Yu Zhang; Xiao-Di Hao; Eiji Iritani; Nobuyuki Katagiri (Chemical Engineering Journal, 2023)

Determination of potential sources of heavy metals in patients with urothelial carcinoma in central Taiwan: a biomonitoring case–control study - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Chih-Da Wu; Chiu-Shong Liu; Mu-Chi Chung; Hui-Tsung Hsu (Environmental Geochemistry and Health, 2023)

Environmentally friendly self-assembly strategy to fabricate novel S and O co-doped carbon nitride aerogel photocatalyst with improved photocatalytic degradation capability - Feng Sun; Da Xu; Yunrui Xie; Feng Liu; Haina Qi; Hong Shao; Ying Yang; Hui Yu; Wensheng Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2023)

Unravelling the role of reactive oxygen species in ultrathin Z-scheme heterojunction with surface zinc vacancies for photocatalytic H2O2 generation and CTC degradation - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Chao Liang; Hai Guo; Ya-Ya Yang; Lu Li (Chemical Engineering Journal, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Capacitively coupled effect and capacitive decoupling of multichannel controlled-source audio magnetotellurics observations - Da Lei; Qi-hui Zhen; Ruo Wang; Chang-min Fu; Hao Ren (Applied Geophysics, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Functional Autapses Form in Striatal Parvalbumin Interneurons but not Medium Spiny Projection Neurons - Xuan Wang; Zhenfeng Shu; Quansheng He; Xiaowen Zhang; Luozheng Li; Xiaoxue Zhang; Liang Li; Yujie Xiao; Bo Peng; Feifan Guo; Da-Hui Wang; Yousheng Shu (Neuroscience Bulletin, 2023)

Joint species distribution models unveil co‐occurrences between freshwater mussels and their fish hosts - Janine P. da Silva; Duarte Vasconcelos Gonçalves; Aina Garcia‐Raventós; Manuel Lopes‐Lima; Simone Varandas; Elsa Froufe; Amílcar Teixeira; Francis K. C. Hui; Ana Filipa Filipe; Ronaldo Sousa (Journal of Biogeography, 2023)
Aim Freshwater mussels are among the most threatened taxa in the world, partially due to the dependence on fish hosts to complete their life cycle. Knowledge about the role of environmental and biotic drivers in determining mussels' distribution is currently lacking. We aimed to assess the role of environmental and biotic drivers in determining the distribution of mussels and their fish hosts and to test if co‐occurrence patterns were able to identify mussel‐host interactions. Location Douro River basin (Iberian Peninsula). Taxon Four freshwater mussels and ten fish hosts. Methods Joint species distribution models (JSDMs) were fitted to presence‐absence records for mussel and fish assemblages. Variance partitioning among environmental variables and latent variables was conducted to determine the environmental versus biotic drivers of species distributions. Resulting matrices of pairwise species co‐occurrences were used to identify co‐occurrence patterns. Results The distribution of host generalist mussel species was mainly explained by environmental variables related to climate and topography. The distribution of the host specialist Margaritifera margaritifera was mainly explained by land use. Strong positive correlations between mussels and the most relevant fish hosts were consistently captured by JSDMs. Co‐occurrence patterns were mainly explained by residual factors, indicating the potential role of biotic interactions. Main Conclusions Biotic interactions were expected to play an important role in explaining mussels' distribution, but the contribution of this factor was only meaningful for the host specialist M. margaritifera . Correlations between mussels and suitable hosts allowed to infer important fish hosts for freshwater mussels in the Douro River basin from distributional data alone. By finding similarities between the ecological requirements of co‐occurring species, conservation measures can be oriented towards several species, which brings a more holistic perspective to the protection of biodiversity.

Appropriate oxygen vacancies and Mo-N bond synergistically modulate charge transfer dynamics of MoO3−x/S-CN for superior photocatalytic disinfection: Unveiling synergistic effects and disinfection mechanism - Ya-Ya Yang; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Hao-Peng Feng; Lu Li; Hui-Yun Liu; Qian-Qian Fan; Meng-Zhu Qin (Journal of Hazardous Materials, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

T-2 toxin-induced intestinal damage with dysregulation of metabolism, redox homeostasis, inflammation, and apoptosis in chicks - Meng Liu; Ling Zhao; Jin-Tao Wei; Yu-Xuan Huang; Mahmoud Mohamed Khalil; Wen-Da Wu; Kamil Kuča; Lv-Hui Sun (Archives of Toxicology, 2023)

Molecular mechanism of di-n-butyl phthalate promotion of bladder cancer development - En-Hui Li; Bai-Hui Xu; Hai-Bin Wei; Yu-Chen Bai; Qi Zhang; Wei-Wen Yu; Zhi-Hui Xu; Xiao-Long Qi; Da-Hong Zhang; Heng Wang (Toxicology in Vitro, 2023)

Synergy between sulfur vacancy and Schottky junction into CoB/ZnIn2S4–S photocatalysts: Oriented charge flow and regulated carriers transfer dynamics to activate reactive oxygen species generation for efficient photocatalytic disinfection - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Meng-Ke Li; Ya-Ya Yang; Ning Tang; Lu Li; Lei Zhang (Journal of Cleaner Production, 2023)

Electrospun self-supporting double Z-scheme tricolor-typed microfiber oriented-heterostructure photocatalyst with highly effective hydrogen evolution and organic pollutants degradation - Feng Sun; Yunrui Xie; Da Xu; Feng Liu; Haina Qi; Qianli Ma; Ying Yang; Hui Yu; Wensheng Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Residential greenness and air pollution's association with nasal microbiota among asthmatic children - Aji Kusumaning Asri; Tsunglin Liu; Hui-Ju Tsai; Hsiao-Yun Lee; Wen-Chi Pan; Chih-Da Wu; Jiu-Yao Wang (Environmental Research, 2023)

Constructing robust cathode/Li interfaces and intensifying ion transport kinetics for PEO-based solid-state lithium-sulfur batteries - Jin Li; Haitao Zhang; Yingyue Cui; Haoran Da; Hui Wu; Yingjun Cai; Suojiang Zhang (Chemical Engineering Journal, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Selection of optimal seismic intensity measures using fuzzy-probabilistic seismic demand analysis and fuzzy multi-criteria decision approach - Ming-Yang Xu; Da-Gang Lu; Xiao-Hui Yu; Ming-Ming Jia (Soil Dynamics and Earthquake Engineering, 2023)

Technological development pathway for carbon neutrality in China - Siyue Guo; Yu Liu; Weichen Zhao; Jiaquan Li; Guangwen Hu; Hui Kong; Yifan Gu; Bang Xu; Xiaodan Huang; Yan Zheng; Shihan Zhang; Da Zhang; et al. (Science Bulletin, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Horticoccus luteus gen. nov., sp. nov., A Novel Member of the Phylum Verrucomicrobia Isolated from a Dichlorodiphenyltrichloroethane (DDT)-Contaminated Orchard Soil - Joon-hui Chung; Ja-Yeon Lee; Geun-Hyung Choi; Miyoung Won; Jehyeong Yeon; Younggun Yoon; Si-Hyun An; Da-Yeon Kim; InCheol Park; Ye-eun Kim; Jae-Hyung Ahn (Current Microbiology, 2022)

Temperate northern hemisphere dominates the global soil CH4 sink - Xin Xu; Da Wei; Ya-hui Qi; Xiao-dan Wang (Journal of Mountain Science, 2022)

Xenoestrogen Status of Wuling Farm to Surrounding Water Bodies: An Application of Biochemical Parameters Using Onychostoma barbatulum - Lin-Yan Liao; Hui-Ling Cheng; Shu-Yin Wang; Shih-Hsiung Liang; Da-Ji Huang (Journal of Marine Science and Engineering, 2022)
The aim of this study was to apply biochemical parameters to Onychostoma barbatulum to understand whether Wuling Farm activities have caused organic pollution from xenoestrogens to flow into surrounding streams and thereby affected area aquatic ecosystems. Individuals of the Taiwan shovel-jaw carp (O. barbatulum) were collected by fyke netting in the Cijiawan, Kaoshan, and Yusheng Rivers in the protected area of Shei-Pa National Park and in the Ikawan River outside the protected areas from 4–5 June 2015 to 20–21 September 2015. The collected male individuals of O. barbatulum were divided into two groups. In the first group monooxygenase (Mon) activity, glutathione S-transferase (GST) activity, and vitellogenin (VTG) concentration in the liver were measured right after they were captured. Those in the second group were acclimated for 14 days and then exposed to 0 (control) or 10 ng/L 17β-estradiol for 10 days and then measured for changes in Mon, GST, and VTG in their livers. The value of VTG concentrations in O. barbatulum individuals collected from the Ikawan River was 2.12 ± 1.62 μg PO42+/g protein, which was the highest among all samples, followed by those collected from the Yusheng River (0.78 ± 1.00 μg PO42+/g protein). Individuals collected from the Yusheng River had the highest liver Mon activity (4.16 ± 1.08△A650/30 min/g protein) and the highest GST activity (1.58 ± 1.13 △A340/20 min/g protein), followed by those from the Ikawan River (Mon: 3.63 ± 1.13 △A650/30 min/g protein; GST: 1.24 ± 0.73 △A340/20 min/g protein). Comprehensive analyses showed that Mon and GST activities and VTG concentrations in livers measured right after being collected were lower than individuals exposed to 10 ng 17β-estradiol/L in the laboratory. Induced VTG concentrations were 9.87 ± 0.89 μg PO42+/g protein, Mon activity 8.02 ± 1.74 △A650/30 min/g protein, and GST activity 3.24 ± 0.62 △A340/20 min/g protein, indicating that farming activities have not significantly affected these aquatic organisms. However, pollution sources are still releasing pollutants containing xenoestrogens into the Yusheng River and Ikawan River. The impact of xenoestrogens is worthy of continuous long-term follow-up monitoring.

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

Correction to: Protective effects of fowl‑origin cadmium‑tolerant lactobacillus against sub‑chronic cadmium‑induced toxicity in chickens - Da‑Wei Chen; Hui‑Jia Li; YinYin Liu; Li‑Na Ma; Jun‑Hua Pu; JunXian Lu; Xiu‑Jun Tang; Yu‑shi Gao (Environmental Science and Pollution Research, 2022)

Protective effects of fowl-origin cadmium-tolerant lactobacillus against sub-chronic cadmium-induced toxicity in chickens - Da-Wei Chen; Hui-Jia Li; YinYin Liu; Li-Na Ma; Jun-Hua Pu; JunXian Lu; Xiu-Jun Tang; Yu-shi Gao (Environmental Science and Pollution Research, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Dissecting the Neural Circuitry for Pain Modulation and Chronic Pain: Insights from Optogenetics - Fang Guo; Yu Du; Feng-Hui Qu; Shi-Da Lin; Zhong Chen; Shi-Hong Zhang (Neuroscience Bulletin, 2022)
Pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage. The processing of pain involves complicated modulation at the levels of the periphery, spinal cord, and brain. The pathogenesis of chronic pain is still not fully understood, which makes the clinical treatment challenging. Optogenetics, which combines optical and genetic technologies, can precisely intervene in the activity of specific groups of neurons and elements of the related circuits. Taking advantage of optogenetics, researchers have achieved a body of new findings that shed light on the cellular and circuit mechanisms of pain transmission, pain modulation, and chronic pain both in the periphery and the central nervous system. In this review, we summarize recent findings in pain research using optogenetic approaches and discuss their significance in understanding the pathogenesis of chronic pain.

Effect of Chromium Supplementation on Blood Glucose and Lipid Levels in Patients with Type 2 Diabetes Mellitus: a Systematic Review and Meta-analysis - Fengyi Zhao; Da Pan; Niannian Wang; Hui Xia; Hong Zhang; Shaokang Wang; Guiju Sun (Biological Trace Element Research, 2022)

Identification and expression analysis of grape LRK10L-2 genes during grape fruit development - Jin-Ping Ma; Xue-Ren Yin; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Sheng-Di Yang; Hui-Ying Jin; Guang-Qi He; Da-Long Guo (Plant Biotechnology Reports, 2022)

Rapid visual detection of porcine reproductive and respiratory syndrome virus via recombinase polymerase amplification combined with a lateral flow dipstick - Xiao-Xiao Tian; Tao Wang; Xing-Yang Cui; Xin-Yi Huang; Yue Sun; Da-Song Xia; Yong-Bo Yang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Resting-state abnormalities in functional connectivity of the default mode network in autism spectrum disorder: a meta-analysis - Qing Wang; Hua-Yun Li; Yun-Da Li; Ya-Ting Lv; Hui-Bin Ma; An-Feng Xiang; Xi-Ze Jia; Dong-Qiang Liu (Brain Imaging and Behavior, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Alpine Hummocks Drive Plant Diversity and Soil Fertile Islands on the Tibetan Plateau - Hui Zhao; Da Wei; Yan Yan; Jianbo Wu; Xiaodan Wang (Wetlands, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Feedbacks of Alpine Wetlands on the Tibetan Plateau to the Atmosphere - Da Wei; Hui Zhao; Lin Huang; Yahui Qi; Xiaodan Wang (Wetlands, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Ultrasonography-Based Qualitative and Quantitative Evaluation Approaches for Pompe Disease - Yueh-Hui Lee; Hong-Jen Chiou; Da-Tian Bau; Dau-Ming Niu; Ting-Rong Hsu; Hsuan-En Huang; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to propose the qualitative and quantitative approaches to evaluate the skeletal muscle ultrasound images of 23 Pompe disease (i.e., acid maltase deficiency, AMD) patients and 14 normal subjects. Methods A cohort of 23 AMD patients and 14 normal subjects has been investigated. We compared the B-mode echo intensity of the rectus femoris muscle with that of its surrounding fat (subcutaneous fat) and proposed a qualitative grading method. Quantitative analysis of the region of interest (ROI) with the echo intensity and the segmented area was also performed. Results Qualitative results showed that AMD patients without clinical symptoms (without undergoing ERT) had the highest distribution of Grade 1, and AMD patients undergoing ERT had the widest distribution of Grade 2, and control group (n = 14) with the highest distribution of Grade 1. Using the segmented area approach, quantitative results showed that AMD patients undergoing ERT had the largest and widest distribution. Meanwhile the control subjects (normal subjects) had the lowest and the narrowest areas. The echo intensity of the segmented ROI of AMD patients undergoing ERT displayed the highest and widest (inhomogeneous) distributions. By contrast, the echo intensity of AMD patients without clinical symptoms was slightly increased and with low inhomogeneity. Conclusion The proposed ultrasonography-based qualitative and quantitative approach may be used to evaluate the severity of muscle destruction for AMD patients. Besides, the quantitative segmented area with regression analysis could help predict the incidence of onset of Pompe disease patients.

Effects of high-intensity interval training on adipose tissue lipolysis, inflammation, and metabolomics in aged rats - Lei Sun; Fang-Hui Li; Tao Li; Zhu Min; Luo-Dan Yang; Hao-En Gao; Da-Shuai Wu; Tian Xie (Pflügers Archiv - European Journal of Physiology, 2020)

Expression and function of FRA1 protein in tumors - Xiaoyan Jiang; Hui Xie; Yingyu Dou; Jing Yuan; Da Zeng; Songshu Xiao (Molecular Biology Reports, 2020)

Protective role of curcumin in cadmium-induced testicular injury in mice by attenuating oxidative stress via Nrf2/ARE pathway - Shu-Hua Yang; Jian-Bin He; Li-Hui Yu; Lin Li; Miao Long; Ming-Da Liu; Peng Li (Environmental Science and Pollution Research, 2019)

IGF-1R/β-catenin signaling axis is involved in type 2 diabetic osteoporosis - Zhi-da Zhang; Hui Ren; Wei-xi Wang; Geng-yang Shen; Jin-jing Huang; Mei-qi Zhan; Jing-jing Tang; Xiang Yu; Yu-zhuo Zhang; De Liang; Zhi-dong Yang; Xiao-bing Jiang (Journal of Zhejiang University-SCIENCE B, 2019)

Effect of locally accumulated crushed stone soil on the infiltration of intense rainfall: a case study on the reactivation of an old deep landslide deposit - Guoxiang Tu; Da Huang; Runqiu Huang; Hui Deng (Bulletin of Engineering Geology and the Environment, 2019)

Correction to: Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2019)

CaMYC, A Novel Transcription Factor, Regulates Anthocyanin Biosynthesis in Color-leaved Pepper (Capsicum annuum L.) - Bo-Ya Lu; Guo-Xin Cheng; Zhen Zhang; Jian-Tian Sun; Muhammad Ali; Qing-Li Jia; De-Xu Luo; Zhen-Hui Gong; Da-Wei Li (Journal of Plant Growth Regulation, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Reactivation of a huge ancient landslide by surface water infiltration - Guo-xiang Tu; Da Huang; Hui Deng (Journal of Mountain Science, 2019)

Exosomes derived from mesenchymal stem cells inhibit mitochondrial dysfunction-induced apoptosis of chondrocytes via p38, ERK, and Akt pathways - Hui Qi; Dan-Ping Liu; Da-Wei Xiao; Da-Chuan Tian; Yong-Wei Su; Shao-Feng Jin (In Vitro Cellular & Developmental Biology - Animal, 2019)

Time Effects on Resting EEG in Children With/Without AD/HD - Da-Wei Zhang; Stuart J. Johnstone; Hui Li; Robert J. Barry; Adam R. Clarke; Qihua Zhao; Yan Song; Lu Liu; Qiujin Qian; Yufeng Wang; Li Sun (Brain Topography, 2019)

Analysis of Rock Mass Stability Based on Mining-Induced Seismicity: A Case Study at the Hongtoushan Copper Mine in China - Jian-po Liu; Shi-da Xu; Yuan-hui Li; Gang Lei (Rock Mechanics and Rock Engineering, 2019)

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

An ensemble-based likelihood ratio approach for family-based genomic risk prediction - Hui An; Chang-shuai Wei; Oliver Wang; Da-hui Wang; Liang-wen Xu; Qing Lu; Cheng-yin Ye (Journal of Zhejiang University-SCIENCE B, 2018)

Perfluoroalkyl Substances (PFASs) in Ten Edible Freshwater Fish Species from Major Rivers and Lakes in Korea: Distribution and Human Exposure by Consumption - Mai Duc Hung; Nguyen Hoang Lam; Hui Ho Jeong; Hyeon Ji Jeong; Da Jin Jeong; Gyeong Hwa Park; Pil Jae Kim; Jeong Eun Oh; Hyeon Seo Cho (Toxicology and Environmental Health Sciences, 2018)

Whole sequence analysis indicates a recent southern origin of Mongolian Y-chromosome C2c1a1a1-M407 - Yun-Zhi Huang; Lan-Hai Wei; Shi Yan; Shao-Qing Wen; Chuan-Chao Wang; Ya-Jun Yang; Ling-Xiang Wang; Yan Lu; Chao Zhang; Shu-Hua Xu; Da-Li Yao; Li Jin; et al. (Molecular Genetics and Genomics, 2018)

Sevoflurane Affects Oxidative Stress and Alters Apoptosis Status in Children and Cultured Neural Stem Cells - Xue Zhou; Dihan Lu; Wen-da Li; Xiao-hui Chen; Xiao-yu Yang; Xi Chen; Zhi-bin Zhou; Jiang-Hong Ye; Xia Feng (Neurotoxicity Research, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

Quantitative proteomics of pomegranate varieties with contrasting seed hardness during seed development stages - Juan Niu; Da Cao; Haoxian Li; Hui Xue; Lina Chen; Beibei Liu; Shangyin Cao (Tree Genetics & Genomes, 2018)

Impact of Bedding Planes on Mechanical Properties of Sandstone - Shan-chao Hu; Yun-liang Tan; Hui Zhou; Wei-yao Guo; Da-wei Hu; Fan-zhen Meng; Zhi-gang Liu (Rock Mechanics and Rock Engineering, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Olfactory Dysfunction in Parkinson’s Disease Patients with the LRRK2 G2385R Variant - Ming Cao; Zhu-Qin Gu; Yuan Li; Hui Zhang; Xiao-Juan Dan; Shan-Shan Cen; Da-Wei Li; Piu Chan (Neuroscience Bulletin, 2016)

Risk assessment of dietary exposure to aluminium in the Chinese population - Ning Ma; Zhao-Ping Liu; Da-Jin Yang; Jiang Liang; Jiang-Hui Zhu; Hai-Bin Xu; Feng-Qin Li; Ning Li (Food Additives & Contaminants: Part A, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

ECV304/C6 coculture model of the BBB coupled with LC–MS analysis for drug screening from Rhubarb extract - Jiang-Feng Yuan; Hui-Hui Ji; Zhi-Jun Qiu; Da-Hong Wang (Medicinal Chemistry Research, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

A baseline study on lipid and fatty acid composition in the pearl oyster, Pinctada fucata - Ya-nan Shen; Dong-ling Zhang; Bo Zhang; Song Jiang; Bo-suo Liu; Gui-ju Huang; Da-hui Yu (Aquaculture International, 2016)

MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Hydrogen peroxide enhances antioxidative defense in the leaves of water caltrop (Trapa bicornis) seedlings treated with lead - Da-Hui Li; Yi Yuan (Biologia, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Isolation and screening of microsatellite markers from the pearl oyster, Pinctada fucata using FIASCO method - DA-HUI YU; NI-NI QU; GUI-JU HUANG (Journal of Genetics, 2015)

Erratum to: Neurogenic differentiation from adipose-derived stem cells and application for autologous transplantation in spinal cord injury - Yong Zhao; Hui Jiang; Xin-wei Liu; Jian-Ting Chen; Liang-Bi Xiang; Da-Peng Zhou (Cell and Tissue Banking, 2015)

Formation of radial symmetric needle-like rosette leaves in Arabidopsis - Jiang-Ping Song; Da-Hui Liu; Yi-Bo Wang; Ya-Na Shi (Biologia, 2015)

Neurogenic differentiation from adipose-derived stem cells and application for autologous transplantation in spinal cord injury - Yong Zhao; Hui Jiang; Xin-wei Liu; Jian-Ting Chen; Liang-Bi Xiang; Da-Peng Zhou (Cell and Tissue Banking, 2015)

Full tensor gravity gradiometry data inversion: Performance analysis of parallel computing algorithms - Zhen-Long Hou; Xiao-Hui Wei; Da-Nian Huang; Xu Sun (Applied Geophysics, 2015)

Laparoscopic versus open distal pancreatectomy for benign or premalignant pancreatic neoplasms: A two-center comparative study - Jia-fei Yan; Tian-tao Kuang; Da-yong Ji; Xiao-wu Xu; Dan-song Wang; Ren-chao Zhang; Wei-wei Jin; Yi-ping Mou; Wen-hui Lou (Journal of Zhejiang University-SCIENCE B, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Increased Expression of TRPC5 in Cortical Lesions of the Focal Cortical Dysplasia - Guang-Zhen Xu; Hai-feng Shu; Hai-Yun Yue; Da-Hai Zheng; Wei Guo; Hui Yang (Journal of Molecular Neuroscience, 2015)

Relationship between haze and acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing - Jin-jun Zhang; Meng-meng Cui; Da Fan; De-shan Zhang; Hui-xin Lian; Zhao-yin Yin; Jin Li (Environmental Science and Pollution Research, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

EGFR-AKT-mTOR activation mediates epiregulin-induced pleiotropic functions in cultured osteoblasts - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Kun Yuan; Da-wei Xu; Jia-jia Chen; Zhi-ming Cui (Molecular and Cellular Biochemistry, 2015)

Long-term morphological response to dredging including cut-across-shoal in a tidal channel-shoal system - Yu-Hai Wang; Chong-Hao Wang; Li-Qun Tang; Da-Bin Liu; Chuan-Sheng Guo; Chun-Jing Liu; Hui-Ming Zhao (Ocean Dynamics, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

A CMS-Related Gene, Ψatp6-2, Causes Increased ATP Hydrolysis Activity of the Mitochondrial F1Fo-ATP Synthase and Induces Male Sterility in Pepper (Capsicum annuum L.) - Jiao-Jiao Ji; Wei Huang; Da-Wei Li; Yan-Xu Yin; Wei-Guo Chai; Zhen-Hui Gong (Plant Molecular Biology Reporter, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

Expression of GLP-1R protein and its clinical role in intrahepatic cholangiocarcinoma tissues - Ben-Dong Chen; Wen-Chao Zhao; Jian-Da Dong; Hui Sima (Molecular Biology Reports, 2014)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

Molecular modeling studies of JNK3 inhibitors using QSAR and docking - Xiang-Xiang Wu; Da-Shun Dai; Xin Zhu; Xiao-Fei Li; Juan Yuan; Xue-Fen Wu; Ming-San Miao; Hua-Hui Zeng; Chun-Lei Zhao (Medicinal Chemistry Research, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Endogenous Subventricular Zone Neural Progenitors Contribute to the Formation and Hyperexcitability of Experimental Model of Focal Microgyria - Hai-Feng Shu; Yong-Qin Kuang; Shi-Yong Liu; Si-Xun Yu; Chun-Qing Zhang; Da-Hai Zheng; Jian-Wen Gu; Hui Yang (Journal of Molecular Neuroscience, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Molecular characterization and expression analysis of a KIFC1-like kinesin gene in the testis of Eumeces chinensis - Jian-Rao Hu; Mei Liu; Da-Hui Wang; Yan-Jun Hu; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

Characterization and cross-species amplification of 11 polymorphic microsatellite loci in Liobagrus marginatoides - Xiang-Yang Jia; Ying-Wen Li; Deng-Qiang Wang; Hui-Wu Tian; Bin Tu; Da-Qing Chen (Conservation Genetics Resources, 2013)

Effects of position within wheat field and adjacent habitats on the density and diversity of cereal aphids and their natural enemies - Zi-Hua Zhao; Cang Hui; Da-Han He; Feng Ge (BioControl, 2013)

In vitro interactions between rat bone marrow-derived endothelial progenitor cells and hepatic stellate cells - Feng Liu; Zhi-da Liu; Nan Wu; Jiang-Hua Wang; Heng-Hui Zhang; Ran Fei; Xu Cong; Hong-song Chen; Lai Wei (In Vitro Cellular & Developmental Biology - Animal, 2013)

Defence responses of pepper (Capsicum annuum L.) infected with incompatible and compatible strains of Phytophthora capsici - Jun-E Wang; Da-Wei Li; Ying-Li Zhang; Qian Zhao; Yu-Mei He; Zhen-Hui Gong (European Journal of Plant Pathology, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Amino-Terminated Generation 2 Poly(amidoamine) Dendrimer as a Potential Broad-Spectrum, Nonresistance-Inducing Antibacterial Agent - Xiaoyan Xue; Xiaoqing Chen; Xinggang Mao; Zheng Hou; Ying Zhou; Hui Bai; Jingru Meng; Fei Da; Guojun Sang; Yukun Wang; Xiaoxing Luo (The AAPS Journal, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Increased Expression of TRPV1 in the Cortex and Hippocampus from Patients with Mesial Temporal Lobe Epilepsy - Fei-Ji Sun; Wei Guo; Da-Hai Zheng; Chun-Qing Zhang; Song Li; Shi-Yong Liu; Qing Yin; Hui Yang; Hai-Feng Shu (Journal of Molecular Neuroscience, 2013)

Comparison of microplate and macrodilution methods in time–kill study of new antimicrobial drugs - Ying Zhou; Zheng Hou; Chao Fang; Xiaoyan Xue; Fei Da; Yukun Wang; Hui Bai; Xiaoxing Luo (Folia Microbiologica, 2013)

Comparative study of four rice cultivars with different levels of cadmium tolerance - Xiao Wang; Zhong-Wei Zhang; Shi-Hua Tu; Wen-Qiang Feng; Fei Xu; Feng Zhu; Da-Wei Zhang; Jun-Bo Du; Shu Yuan; Hong-Hui Lin (Biologia, 2013)

Preparation and Characterization of Stable pH-Sensitive Vesicles Composed of α-Tocopherol Hemisuccinate - Huan Xu; Yi-Hui Deng; Kai-Qian Wang; Da-Wei Chen (AAPS PharmSciTech, 2012)

X-ray structure study of ranaconitine hydrobromide - Jun-Hui Zhou; Yang Li; Lei Zhang; Da-Qi Wang (Natural Product Research, 2012)

Characterization and expression pattern of KIFC1-like kinesin gene in the testis of the Macrobrachium nipponense with discussion of its relationship with structure lamellar complex (LCx) and acroframosome (AFS) - Yan-Ting Wang; Huan Mao; Cong-Cong Hou; Xiao Sun; Da-Hui Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Three new secolignan glycosides from Urtica fissa E. Pritz - Bao-min Feng; Hai-hong Qin; Hui-guo Wang; Li-ying Shi; Da-yong Yu; Bao-quan Ji; Qi Zhao; Yong-qi Wang (Journal of Natural Medicines, 2012)

Cognitive and serum BDNF correlates of BDNF Val66Met gene polymorphism in patients with schizophrenia and normal controls - Xiang Yang Zhang; Da Chun Chen; Mei Hong Xiu; Colin N. Haile; Xingguang Luo; Ke Xu; Hui Ping Zhang; Lingjun Zuo; Zhijun Zhang; Xiangrong Zhang; Therese A. Kosten; Thomas R. Kosten (Human Genetics, 2012)

Characterization and expression analysis of prohibitin in the testis of Chinese mitten crab Eriocheir sinensis - Huan Mao; Da-Hui Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Gene expression profiles of prohibitin in testes of Octopus tankahkeei (ot-phb) revealing its possible role during spermiogenesis - Hai-Tao Mao; Da-Hui Wang; Zhou Lan; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Molecular characterization of a KIF3A-like kinesin gene in the testis of the Chinese fire-bellied newt Cynops orientalis - Jian-Rao Hu; Na Xu; Fu-Qing Tan; Da-Hui Wang; Mei Liu; Wan-Xi Yang (Molecular Biology Reports, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Immunolocalization of chloride transporters to gill epithelia of euryhaline teleosts with opposite salinity-induced Na+/K+-ATPase responses - Cheng-Hao Tang; Lie-Yueh Hwang; I-Da Shen; Yu-Hui Chiu; Tsung-Han Lee (Fish Physiology and Biochemistry, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Sub-chronic effect of perfluorooctanesulfonate (PFOS) on the balance of type 1 and type 2 cytokine in adult C57BL6 mice - Guang-Hui Dong; Miao-Miao Liu; Da Wang; Li Zheng; Zai-Fu Liang; Yi-He Jin (Archives of Toxicology, 2011)

Polyethylenimine-cyclodextrin-tegafur conjugate shows anti-cancer activity and a potential for gene delivery - Qi-da Hu; Hui Fan; Wei-jian Lou; Qing-qing Wang; Gu-ping Tang (Journal of Zhejiang University-SCIENCE B, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Warfarin resistance test and polymorphism screening in the VKORC1 gene in Rattus flavipectus - Bao-Huan Huang; Zhi-Yong Feng; Ling-Fen Yue; Dan-Dan Yao; Zhi-Xiang Gao; Da-Wei Wang; Xiao-Hui Liu (Journal of Pest Science, 2011)

Blood cells of a sisorid catfish Glyptosternum maculatum (Siluriformes: Sisoridae), in Tibetan Plateau - Hui Juan Zhang; Cong Xin Xie; Da Peng Li; Hai Ping Liu; Xue Feng Yang (Fish Physiology and Biochemistry, 2011)

Seasonal and interannual variations in carbon dioxide exchange over a cropland in the North China Plain - HUI‐MIN LEI; DA‐WEN YANG (Global Change Biology, 2010)
In China, croplands account for a relatively large form of vegetation cover. Quantifying carbon dioxide exchange and understanding the environmental controls on carbon fluxes over croplands are critical in understanding regional carbon budgets and ecosystem behaviors. In this study, the net ecosystem exchange (NEE) at a winter wheat/summer maize rotation cropping site, representative of the main cropping system in the North China Plain, was continuously measured using the eddy covariance technique from 2005 to 2009. In order to interpret the abiotic factors regulating NEE, NEE was partitioned into gross primary production (GPP) and ecosystem respiration ( R eco ). Daytime R eco was extrapolated from the relationship between nighttime NEE and soil temperature under high turbulent conditions. GPP was then estimated by subtracting daytime NEE from the daytime estimates of R eco . Results show that the seasonal patterns of the temperature responses of R eco and light‐response parameters are closely related to the crop phenology. Daily R eco was highly dependent on both daily GPP and air temperature. Interannual variability showed that GPP and R eco were mainly controlled by temperature. Water availability also exerted a limit on R eco . The annual NEE was −585 and −533 g C m −2 for two seasons of 2006–2007 and 2007–2008, respectively, and the wheat field absorbed more carbon than the maize field. Thus, we concluded that this cropland was a strong carbon sink. However, when the grain harvest was taken into account, the wheat field was diminished into a weak carbon sink, whereas the maize field was converted into a weak carbon source. The observations showed that severe drought occurring during winter did not reduce wheat yield (or integrated NEE) when sufficient irrigation was carried out during spring.

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Treadmill pre-training suppresses the release of glutamate resulting from cerebral ischemia in rats - Jie Jia; Yong-Shan Hu; Yi Wu; Hui-Xian Yu; Gang Liu; Da-Nian Zhu; Chun-Mei Xia; Zhi-Juan Cao; Xi Zhang; Qing-Chuan Guo (Experimental Brain Research, 2010)

Mitochondrial functions on oocytes and preimplantation embryos - Li-ya Wang; Da-hui Wang; Xiang-yang Zou; Chen-ming Xu (Journal of Zhejiang University-SCIENCE B, 2009)

Potential ecological risk of cadmium, lead and arsenic in agricultural black soil in Jilin Province, China - Hui-cong Cao; Zhao-qing Luan; Jin-da Wang; Xue-lin Zhang (Stochastic Environmental Research and Risk Assessment, 2009)

Functional expression of an earthworm fibrinolytic enzyme in Escherichia coli - Da-hui Li; Wei Tong; Yan-fang Yang (World Journal of Microbiology and Biotechnology, 2008)

Formation of archegonium chamber is associated with nucellar-cell programmed cell death in Ginkgo biloba - Da-Hui Li; Xiong Yang; Ke-Ming Cui (Protoplasma, 2007)

Co-transformation of gene expression cassettes via particle bombardment to generate safe transgenic plant without any unwanted DNA - Yan Zhao; Qian Qian; Hui-Zhong Wang; Da-Nian Huang (In Vitro Cellular & Developmental Biology - Plant, 2007)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Common pearl oysters in China, Japan, and Australia are conspecific: evidence from ITS sequences and AFLP - Da Hui YU; Xiaoping JIA; Ka Hou CHU (Fisheries Science, 2006)

Enhanced degradation of carbon tetrachloride by surfactant-modified zero-valent iron - Ya-feng Meng; Bao-hong Guan; Zhong-biao Wu; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Metabolic effects of telmisartan in spontaneously hypertensive rats - Yong-Qi Li; Hui Ji; Yi-Hua Zhang; Da-Yong Ding; Xiao-Lei Ye (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Characterization of on-road CO, HC and NO emissions for petrol vehicle fleet in China city - Hui Guo; Qing-yu Zhang; Yao Shi; Da-hui Wang; Shu-ying Ding; Sha-sha Yan (Journal of Zhejiang University-SCIENCE B, 2006)

Anselmella malacia, a new pest wasp (Hymenoptera: Chalcidoidea: Eulophidae) reared fromSyzygium samarangense in Malaysia - Hui Xiao; Ling-Na Xu; Da-Wei Huang; Zhong-Yi Zhao (Phytoparasitica, 2006)

Distribution of lead in urban soil and its potential risk in Shenyang City, China - Jin-da Wang; Hui-min Ren; Jing-shuang Liu; Jun-bao Yu; Xue-lin Zhang (Chinese Geographical Science, 2006)

Hg0 absorption in potassium persulfate solution - Qun-feng Ye; Cheng-yun Wang; Da-hui Wang; Guan Sun; Xin-hua Xu (Journal of Zhejiang University-SCIENCE B, 2006)

Testifying the rice bacterial blight resistance gene xa5 by genetic complementation and further analyzing xa5 (Xa5) in comparison with its homolog TFIIAγ1 - Guang-Huai Jiang; Zhi-Hui Xia; Yong-Li Zhou; Jia Wan; Da-Yong Li; Run-Sheng Chen; Wen-Xue Zhai; Li-Huang Zhu (Molecular Genetics and Genomics, 2006)

Changes in purine content of tilapia surimi products during processing - Shyi-Neng LOU; Hui-Huang CHEN; Po-Yang HSU; Da-Hsuan CHANG (Fisheries Science, 2005)

Study on US/O3 mechanism in p-chlorophenol decomposition - Xian-wen Xu; Xin-hua Xu; Hui-xiang Shi; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2005)

Ozonation with ultrasonic enhancement of p-nitrophenol wastewater - Xian-wen Xu; Hui-xiang Shi; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2005)

Simultaneous removal of nitrate and heavy metals by iron metal - Zhi-wei Hao; Xin-hua Xu; Jian Jin; Ping He; Yong Liu; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2005)

A taxonomic study ofNorbanus Walker (Hymenoptera: Pteromalidae) from China - Hui Xiao; Da-Wei Huang; Lei Sun (Phytoparasitica, 2005)

Ovipositor length of threeApocrypta species: Effect on oviposition behavior and correlation with syconial thickness - Wen-Quan Zhen; Da-Wei Huang; Jin-Hua Xiao; Da-Rong Yang; Chao-Dong Zhu; Hui Xiao (Phytoparasitica, 2005)

Reductive denitrification of nitrate by scrap iron filings - Zhi-wei Hao; Xin-hua Xu; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2005)

OsPIPK1, a Rice Phosphatidylinositol Monophosphate Kinase, Regulates Rice Heading by Modifying the Expression of Floral Induction Genes - Hui Ma; Shu-Ping Xu; Da Luo; Zhi-Hong Xu; Hong-Wei Xue (Plant Molecular Biology, 2004)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)